THE USE OF MULTIMEDIA AS AN EFFORT TO IMPROVE ELEMENTARY TEACHER COMPREHENSION ABILITY AND CREATIVE THINKING SKILLS IN FOLLOWING SCIENCE STUDY COURSES - Oding Sunardi; Yudhie Suchyadi; Eka Suhardi; Layung Paramesti Martha (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The research objective was to improve the understanding and creative thinking skills of elementary teacher as prospective teachers in following science courses. The research design used is to make elementary teacher groups into small groups. During the learning process, observations about elementary teacher cooperation during learning with multimedia media were carried out to assess their understanding and creative thinking skills. The results of the observations of each cycle were evaluated as material for reflection in the next cycle to improve college student understanding and creative thinking skills in accordance with predetermined targets. Data analysis was carried out by descriptive quantitative. From the results of the T-test, the results, it was found that there were significant differences. This means that understanding of science process concepts and skills increases after prospective student teachers experience the learning process using multimedia. From the results of the average value of understanding the concept, increasing from 39.86%Â  to 88.22%. and science process skills increased the average value from 49.89% to 86.44%. 92% of college student gave a positive response, namely agreeing and strongly agreeing that the science lecture process using multimedia learning media can improve science process skills and understanding of material in science subjects for elementary teacher education college student. Keywords: multimedia; comprehension ability; creative thinking skills.Â